(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Anovulation as understood in Ayurveda, can be correlated with terms such as Alpapushpa/Nashtartava arising primarily due to vitiation in majorly Vata dosha, Rasavaha srotodushti and Agnimandya. This case report highlights the successful Ayurvedic management of a 26-year-old woman with anovulatory infertility who had been unable to conceive for three years. After undergoing extensive allopathic treatments without success, she opted for Ayurvedic management, which included Virechana and Uttara basti. The combination of these treatment helped restore Shuddha Kshetra (uterus), balances the Agni, and proper formation and improvement in quality of Artava. Result: After three months of Ayurvedic management, the patient successfully conceived and delivered a healthy baby. This case underscores the potential of Ayurvedic approach in managing anovulatory infertility and improving reproductive outcomes.